A three parallel branches harmonic model with adaptive capability of operating state variation - Youhang Yang; Shaorong Wang; Jiaxuan Ren; Yao Guo; Siyuan Chen; Mingming Shi; Xian Zheng (International Journal of Electrical Power & Energy Systems)
The wide application of power electronic equipment has exacerbated the harmonic distortion in power systems. More accurate harmonic models are urgently needed to evaluate and mitigate harmonic issues. To address this challenge, we propose a three parallel branches model (TPBM) with adaptive capability of operating state variation. Firstly, the accuracy of current general harmonic models is analyzed through Taylor expansion. Secondly, the structure of TPBM is proposed and a parameter calculation method is provided for individual operating state. TPBM comprehensively incorporates the effects of variations in different order voltages and characteristic parameters of harmonic source with respect to the steady-state operating point, and theoretically can achieve higher accuracy than traditional models. Furthermore, an adaptive TPBM for harmonic source operating state variations based on Stacking ensemble learning technology is proposed, the construction process and training strategy of the Stacking model are also elaborated. Finally, simulations and experiments are conducted to validate the effectiveness and accuracy of the proposed method. The results demonstrate that the adaptive TPBM exhibits enhanced adaptability to variations in harmonic source operating states and achieves superior estimation accuracy for harmonic currents compared to the crossed frequency admittance matrix model and the complex partial least squares method under both single and multiple operating conditions.